FAKTOR-FAKTOR YANG BERKAITAN TERHADAP FINANCIAL PERFORMANCE PADA SEKTOR ANEKA INDUSTRI - Leonardi, Oktavianus; Dermawan, Elizabeth Sugiarto (Jurnal Paradigma Akuntansi, 2025)
The purpose of this research was to find out and find empirical evidence about the relationship of leverage, firm size, and liquidity on financial performance in miscellaneous industrial sectors listed on the Indonesia Stock Exchange in 2019 - 2021. This research uses 25 companies in miscellaneous industrial sectors and the samples were selected through a purposive sampling technique with a non-parametric test. Data processing techniques uses the spearman rank correlation test which is processed using SPSS version 25 and Microsoft Excel 2016. The results of this research indicate that leverage is negative correlated, significant, and has a sufficient relationship to financial performance, firm size is positive correlated, insignificant, and has a weakly relationship to financial performance, and liquidity is positive correlated, significant, and has a sufficient relationship to financial performance.